Ceramic Granules with Plant Biostimulant Effects Based on Silicon-Rich Biomaterials - Mălina Deșliu-Avram; Orsolya-Csilla Ráduly; Luiza Capră; Marius Ghiurea; Ioana Popa-Tudor; Diana Constantinescu-Aruxandei; Mariana Pătrașcu; Josef Fazakas; Florin Oancea (Proceedings)
Bentonite-based porous ceramics act as a slow release of adsorbed phosphate for plant growth [...]